RECONSTRUCTION OF THE SPISMENT OF WOMEN LIVING WITH HIV IN WEST SUMATRA - Azizah Meria; Muhammad Fauzi; Lukmanul Hakim; Lidya Arman (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This community service program aimed to reconstruct the spiritual, health, and mental aspects (Spisment) of women living with HIV/AIDS in West Sumatra. Employing a Community-Based Research (CBR) approach, the program engaged 23 participants from various regions. The primary focus was to address negative stigma, physical health needs, and mental and spiritual recovery. Findings indicate that the Spisment reconstruction was effective in enhancing optimism, self-acceptance, and overall quality of life. This approach not only strengthened spiritual dimensions but also provided significant physical and mental health benefits. It is anticipated that these research findings will contribute positively to the development of sustainable community service programs for people living with HIV/AIDS in Indonesia.